2013
DOI: 10.15376/biores.8.4.5536-5548
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Biochar on Microbial Activities of Heavy Metals Contaminated Paddy Fields

Abstract: dBiochar (BC) amendments might decrease the bioavailability of metals in soils that are contaminated with heavy metals. In general, soil microbial communities are sensitive to changes in soil property changes. Microbial communities were tested in a Cd-and Pb-polluted paddy field in southern China. BC was applied as a basal soil amendment before rice transplantation in 2009. The BC was applied at rates of 0, 10, 20, and 40 tons per hectare. Soil heavy metal fractions with sequential extraction procedure, soil m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(25 citation statements)
references
References 43 publications
4
21
0
Order By: Relevance
“…3). As shown in the work by Cui et al (2013), biochar amendment reduced Cd and Pb bioavailability while increased microbial abundance and biochemical activity. This is also consistent with our previous finding in a microbial study by Liu et al (2012a) that metal pollution increased soil basal respiration, and in a field soil respiration measurement that soil CO 2 evolution was increased in the metal-polluted rice soil over the unpolluted one .…”
Section: Discussionsupporting
confidence: 53%
“…3). As shown in the work by Cui et al (2013), biochar amendment reduced Cd and Pb bioavailability while increased microbial abundance and biochemical activity. This is also consistent with our previous finding in a microbial study by Liu et al (2012a) that metal pollution increased soil basal respiration, and in a field soil respiration measurement that soil CO 2 evolution was increased in the metal-polluted rice soil over the unpolluted one .…”
Section: Discussionsupporting
confidence: 53%
“…The presence of potentially toxic substances, toxic heavy metals and polycyclic aromatic hydrocarbons (PAHs) in biochar and usually strongly alkaline pH may constitute a serious threat to soil quality, and in particular, to its biological life (Yang et al, 2016). Organic and inorganic contaminants introduced into the soil with biochar can have a significant impact on the population of microorganisms (Cui et al, 2013). The present study demonstrated that both rates (2.25 and 5 t ha -1 DM) of biochar added to the soil had a beneficial effect on dehydrogenases activity in the 2 nd and 3 rd year of the experiment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the sorption of organic C and organically bound nutrients on biochar may hinder soil microbial growth (Elzobair et al 2016). Cui et al (2013) also reported that heavy metals (Pb and Cd) in soil alter diversity, activities, and population size of microorganisms. Biochar application alters soil pH and reduced the heavy-metal bioavailability.…”
Section: Response Of Soil Microbes To Biochar Amendment In Contaminatmentioning
confidence: 99%